2018
DOI: 10.1007/s10912-018-9529-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Service Learning in Medical Education: An Ethical Analysis of the Five-Year Alternative Curriculum at Stritch School of Medicine

Abstract: In this article, the author explores a model of alternative medical education being pioneered at Loyola University Chicago Stritch School of Medicine. The five-year Global Health Fieldwork Fellowship (GHFF) track allows two students per year to complete an extra year of medical education while living and working in a free rural clinic in the jungle lowlands of Bolivia. This alternative curricular track is unique among other existing models in that it is (a) longitudinally immersive for at least one full additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…SL has been argued to transform student perspectives on humanism in medicine, including the perspectives of students who respect and empathise with the struggles and strengths of their patients and peers [38]. For example, the Loyola University Chicago Stritch School of Medicine proposed a 5year Global Health Fieldwork Fellowship track that was grounded in clinical and service learning, doing so to foster the development of prosocial values, such as professionalism, advocacy, and social justice in their medical students [39]. SL programmes involving work with the homeless have also enhanced the professional and personal education of medical students by improving their understanding of biopsychosocial problems and by developing their empathy, compassion, and social awareness [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…SL has been argued to transform student perspectives on humanism in medicine, including the perspectives of students who respect and empathise with the struggles and strengths of their patients and peers [38]. For example, the Loyola University Chicago Stritch School of Medicine proposed a 5year Global Health Fieldwork Fellowship track that was grounded in clinical and service learning, doing so to foster the development of prosocial values, such as professionalism, advocacy, and social justice in their medical students [39]. SL programmes involving work with the homeless have also enhanced the professional and personal education of medical students by improving their understanding of biopsychosocial problems and by developing their empathy, compassion, and social awareness [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to nancial resources, some papers recognised the use of other resources. Several papers identi ed that elective students use the supervising clinician's time [2,11,26],…”
Section: Use Of Limited Local Resourcesmentioning
confidence: 99%
“…The second theme which emerged was "negative impact on patient care". When looking at the papers addressing limited local resources, it was found that 6 of them mentioned that visiting students may have a detrimental effect on patient care [2,[9][10][11]25,26]. In a series of interviews with supervisors of elective students in 22 countries, Bozinoff and colleagues found that "host supervisors identi ed potential harms to patient care that might arise in the presence of visiting medical students, including harms associated with differing standards of care, longer wait times, lack of cultural competency, and language barriers between students, patients and staff" [2].…”
Section: Inductive Themes Emerging From the Papers: Negative Impacts ...mentioning
confidence: 99%
“…Given the numerous benefits to integrative service learning cited in previous literature, we hope to expand experiential integrative service learning opportunities for medical students at other local organizations related to food security, such as additional urban farms or food banks. [9][10][11][12][13] After scaling up a pilot program that includes more participants than the current study, our hope is that all medical students at our institution will have opportunities and strong encouragement to participate in service learning related to food insecurity.…”
Section: Rea Almentioning
confidence: 99%
“…10,11 Integrative service learning programs at US medical schools have demonstrated success in teaching medical students professionalism, social justice, advocacy skills, and patient communication strategies. 12,13 It is also recommended that medical education integrates experiential service learning to improve understanding of social determinants of health, including food insecurity, to improve clinical skills and improve population health. 14 The Liaison Committee on Medical Education (LCME) standards require that medical education provides opportunities for service learning activities, yet many schools do not provide structured activities or enforce participation.…”
Section: Introductionmentioning
confidence: 99%